Biogeochemical and hydrochemical investigations on sediment cores from thermokarst terrain on the Baldwin Peninsula, northwestern Alaska - Seemann, Fabian; Frauhammer, Carolin; Ebel, Lars; Lindemann, Justin; Mollenhauer, Gesine; Eulenburg, Antje; Weiner, Mikaela; Meyer, Hanno; Strauss, Jens (PANGAEA, 2025)
In March 2024, sediment cores were collected along two land-ocean transects along the coast of the Baldwin Peninsula (Alaska). Undisturbed permafrost upland, thermokarst lake, drained lake basin and nearshore marine positions were considered. While Transect 0 (T0) is characterized by a recently drained lake (drainage event in 2022), Transect 1 (T1) is characterized by a semi-drained lake basin. The chosen transects represent typical landscape dynamics of the region which have implications on organic matter alteration. In particular, both mentioned landforms were found to maintain taliks. Biogeochmical and hydrochemical investigations on sediments and pore water/ice provide insights into ground conditions and organic carbon degradation. With the exception of radiocarbon dates (MICADAS laboratory, AWI Bremerhaven) and isotope data (ISOLAB Facility, AWI Potsdam), laboratory analyses were conducted at the Permafrost Research Section (AWI Potsdam).
Keywords: Arctic; organic matter; Permafrost; pore water; sediment; talik; thermokarst